Mapping food surveillance chains through different sectors - Amato, Laura; Benedetti, Guido; Di Giuseppe, Paola; Hénaux, Viviane; Lailler, Renaud; Nordeng, Zuzana; Scharffenberg, Tora Alexandra Ziesler; Skjerdal, Taran; Cito, Francesca (Frontiers in Public Health, 2023)
European countries are investing in strengthening disease surveillance from a One Health (OH) perspective. During the MATRIX project, in the context of the One Health European Joint Programme, existing surveillance chains across the sectors of animal health, food safety, and public health have been investigated through questionnaires. Provided information has then been selected to be displayed in a single slide using an implemented mapping template. Two real-life scenarios are presented as case studies: the surveillance activities in place in France for Salmonella in the pork meat food chain, and in Norway for Listeria monocytogenes in the dairy food chain. The results collected through the questionnaires and the lessons learnt during the mapping process are reported, to share the advantages and drawbacks of the methodology. Moreover, the presented template could be adjusted and applied to different contexts. Mapping the components of existing disease surveillance systems is a fundamental step in understanding the relationships between its components, and subsequently facilitating their collaboration and integration under a OH approach.